The Influence of Project-Based Learning Method in Online Learning on the Cognitive Abilities - Koerniawati, Avivah; Sintawati, Mukti (International Journal of Learning Reformation in Elementary Education, 2024)
Effective education is one that explores and maximizes students' potential by creating learning experiences that fully engage them. This research aims to investigate the impact of the Project-Based Learning (PBL) method on the cognitive abilities of 5th-grade students during online learning. This study adopts a quasi-experimental design with the non-equivalent control group approach, utilizing purposive sampling. The sample comprises 20 students in the experimental group and 21 students in the control group. Research instruments include observation guidelines, cognitive ability tests, and documentation checklists. Data analysis involves tests for normality, homogeneity, and hypothesis testing using independent sample t-tests and paired sample t-tests. Results indicate a significant improvement in cognitive abilities in the experimental group, as evidenced by the paired sample t-test with a calculated t-value of 11.048 higher than the critical t-value of 2.086. This suggests that the Project-Based Learning method has a positive influence on the cognitive abilities of 5th-grade  students. The findings support the conclusion that the implementation of Project-Based Learning in online education has a notable impact on the cognitive skills.